2015
DOI: 10.1128/aac.03342-14
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Rescue Screen Identifies a Plasmodium falciparum Apicoplast Inhibitor Targeting MEP Isoprenoid Precursor Biosynthesis

Abstract: The apicoplast is an essential plastid organelle found in Plasmodium parasites which contains several clinically validated antimalarial-drug targets. A chemical rescue screen identified MMV-08138 from the "Malaria Box" library of growth-inhibitory antimalarial compounds as having specific activity against the apicoplast. MMV-08138 inhibition of blood-stage Plasmodium falciparum growth is stereospecific and potent, with the most active diastereomer demonstrating a 50% effective concentration (EC 50 ) of 110 nM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(120 citation statements)
references
References 42 publications
5
109
0
Order By: Relevance
“…In data from parasite clone tree culture experiments13, some subclones from HB3-P and W2 contained the premature stop codon allele while others did not. The nonsense mutation in Epac in the Dd2 clone has been previously noted14, as has the separate stop codon in W215. In summary, most of the laboratory-adapted strains have evidently acquired one or more loss-of-function mutations in Epac or in an ApiAP2 gene.…”
Section: Resultsmentioning
confidence: 65%
“…In data from parasite clone tree culture experiments13, some subclones from HB3-P and W2 contained the premature stop codon allele while others did not. The nonsense mutation in Epac in the Dd2 clone has been previously noted14, as has the separate stop codon in W215. In summary, most of the laboratory-adapted strains have evidently acquired one or more loss-of-function mutations in Epac or in an ApiAP2 gene.…”
Section: Resultsmentioning
confidence: 65%
“…This simple chemical rescue demonstrated that the only essential metabolic function of the apicoplast in blood-stage Plasmodium is the biosynthesis of isoprenoid precursors. IPP supplementation can apparently rescue parasites from any apicoplast dysfunction, making it a nifty tool to study apicoplast biology including identification of antimalarials with unknown targets as anti-apicoplast agents (Wu et al, 2015), and even perturbations of essential gene products (e.g. expression of a dominant-negative SufC, a member of the iron sulphur complex generating system in the apicoplast) (Gisselberg et al, 2013).…”
Section: Making the Apicoplast Disappearmentioning
confidence: 99%
“…For example, IPP supplementation has been shown to allow parasite growth during treatment with either the DXR inhibitor, fosmidomycin (FSM), or the IspD inhibitor, 1 R ,3 S -MMV008138202128. In order to determine whether BITZ inhibition was specific to activity against the MEP pathway, we tested for IPP rescue during treatment with compound 8 .…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a chemical rescue screen identified 4 (1 R ,3 S -MMV008138) from the Medicines for Malaria Venture (MMV) “malaria box” as a potent inhibitor of P. falciparum IspD ( Pf IspD), showing nanomolar inhibition of recombinant enzyme activity and sub-micromolar inhibition of parasite growth (Fig. 2)19202122.…”
mentioning
confidence: 99%